MICROBIOLOGICAL INDICES OF MEAT PRODUCTS AND MEAT DURING FAIR EVENTS IN KYIV - Kit A. А.; Mykhailiutenko, S. M.; Kruchynenko, O. V.; Yevstafieva, V. O.; Melnychuk, V. V. (Scientific Progress & Innovations, 2019)
Meat and various meat products are an important part of the human diet. These products are useful for the human organism as they contain macro- and microelements, vitamins, and they are also a source of pro-tein and essential amino acids. At the same time, these products can be rather harmful to the human health, because of violating technological processes connected with their manufacturing, storing and transporting. That is why the quality control of meat products at all the stages including manufacturing and selling is an important issue to be solved. So, the purpose of the study was to establish separate safety indices of meat and meat products during fair events in Kyiv. The results of the official laboratory testing of such raw products as beef, pork, chicken and turkey meat, sausages, boiled, semi-smoked sausage, ham and brisket became the material of the study. The conducted monitoring showed that the residues of antibiotics in animal meat of and meat products were not detected. All the examined samples of meat corresponded to the veterinary- sanitary requirements as to general bacterial contamination. The number of mesophilic, aerobic and faculta-tive anaerobic microorganisms in finished meat products was within the standard limits. At the same time, the violation of the requirements of the National Standard of Ukraine 4436:2005 was established as to the presence of E. coli group in the finished meat products. It was proved that, concerning sanitary indices, nine samples did not correspond to the regulatory documents, which may testify to violating the conditions of their processing, storing, transporting, and selling. According to the results of the conducted monitoring of animal meat microbiological indices, it was established, that the bacteria of E. coli group exceeded the max-imum permissible levels in only one sample of pork (6.3×103 colony-forming u/g). According to the current requirements as to residual micro-flora in sausages, the content of anaerobic spore sulfite-reducing bacteria (in 0.1 g), salmonella (in 25 g), protea (in 1 g) and coagulase-positive S. aureus (in 1 g) were not found in the tested samples. In addition to the microorganisms that are regulated by the above mentioned require-ments, there were no L. monocytogenes in the examined samples of meat. The practical significance of the paper consists in the increased control of food products’ safety by veter-inary medicine experts during conducting fairs.